2004
DOI: 10.1111/j.1547-5069.2004.04021.x
|View full text |Cite
|
Sign up to set email alerts
|

A Meta‐Analysis of Predictors of Positive Health Practices

Abstract: Findings enable health care professionals and researchers designing intervention studies to use the strongest predictors identified in this meta-analysis to promote positive health practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
2
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 40 publications
(21 reference statements)
7
71
2
4
Order By: Relevance
“…It is possible that programs directed towards enhancing adolescents resistance to social pressures to, e.g., smoke or drink, may be helpful in assisting the majority of adolescents to remain non-smokers and non-drinkers. These findings enable health care professionals and researchers designing intervention studies to use the strongest predictors identified in this study to promote positive health practices [32].…”
Section: Discussionmentioning
confidence: 94%
“…It is possible that programs directed towards enhancing adolescents resistance to social pressures to, e.g., smoke or drink, may be helpful in assisting the majority of adolescents to remain non-smokers and non-drinkers. These findings enable health care professionals and researchers designing intervention studies to use the strongest predictors identified in this study to promote positive health practices [32].…”
Section: Discussionmentioning
confidence: 94%
“…Li te ra tu re, also, fo und a po si ti ve re la ti ons hip bet we en edu ca ti on, monthly in co me level, pro fes si o nal sta tus and per ce i ved he alth, and it has be en de mons tra ted that as edu ca ti o nal and inco me le vels fall, a per son's per cep ti on of ge ne ral health de te ri o ra tes. 16,17,22,23 Ba la ba no va et al 17 ha ve as cer ta i ned that the le vel of per ce i ved he alth was cor re la ted par ti cu larly with fi nan ci al hard ships expe ri en ce; Stronks et al 22 stated that per ce i ved he alth had a stron ger re la ti ons hip with in co me le vel than with ot her so ci o-eco no mic va ri ab les; and Bil kis et al 18 reported that as pe op le's in co me le vel dec re a ses, the per cep ti on of ge ne ral he alth de te ri o ra tes: low inco me gro ups usu ally li ve in po or dis tricts with inade qu a te in fras truc tu re and ad ver se en vi ron men tal con di ti ons. Hos ti le li ving con di ti ons of eco lo gi cal and in di vi du al ori gin not only af fect pe op le's he alth un fa vo rably but al so in cre a se the im pa ir ment of both physi cal and men tal he alth per cep ti on.…”
Section: şEnol Ve Arkmentioning
confidence: 99%
“…9,[16][17][18][19][20] The re la ti ons hip bet we en low edu ca ti o nal le vel and po o rer SRH can be exp la i ned by the un fa vo rable li ving con di ti ons of the low so ci o-eco no mic le vel gro up 21 , and low le vel of edu ca ti on. In co me and profes si o nal sta tus can not only ne ga ti vely af fect uti li zati on of da ily op por tu ni ti es and fa ci li ti es of any kind, but al so cre a te ge ne ral so ci o-cul tu ral cir cums tan ces that can ne ga ti vely im pact he alth.…”
Section: şEnol Ve Arkmentioning
confidence: 99%
“…Marriage increased applications as much as five times (Table 4). In the previous studies, 33,34 too; marriage was considered as a primary determinant of positive health and it was shown to be a significant variable for the increase in health services utilization. Marriage -causing some kind of changes in life style, health/illness awareness, pregnancy, birth and miscarriage problems; and also, facilitating postponed /hidden problems due to social stigmatization-may relatively increase the health services utilization.…”
Section: Ci: Confidence Intervalmentioning
confidence: 99%
“…In the studies, it was found out that those with a poor perceived health saw the doctors more; had more medical consultations on the phone, were hospitalized more and were examined more by a private doctor. 34,[40][41][42][43][44] In the literature, as a result, several studies demonstrated that self-rated health was an important predictor of health services utilization. 6,7,32,41,43 In our research, the presence of chronic disease was the second determinant factor for health service utilization after marital status, and increased the applications 2.5 times more (Table 4).…”
Section: Ci: Confidence Intervalmentioning
confidence: 99%